Orthopedic Surgeries of Lower Limb under Combined Femoral and Sciatic Nerve Block: A Comparative Study in RMCH & RC - Kumar, Dr. Praveen; Kaushik, Dr. Atul (International Journal of Innovative Research in Medical Science, 2018)
The best option for life-saving operations is regional block anesthesia where both general and central neuraxialanesthesia are risky. It does not require fasting, special preparation, or preoperative optimization and can be given in emergency conditions.[1] Also peripheral nerve blocks (PNBs) are preferred for lower limb surgeries and orthopaedic surgeries because of peripheral location of surgical site and the potential to block pain pathways at multiple levels.[2] Furthermore, better cardio respiratory stability is observed with peripheral nerve blocks as central neuraxial blockade is having side effects such as hypotension, bradycardia, meningitis, postdural puncture headache, neurological deficit, etc.[3] Advancement in the newer techniques such as peripheral nerve stimulator and ultrasound anesthesia has shifted from general anesthesia (GA) and central neuraxial blockade for isolated limb surgery to peripheral nerve blocks.[4] But still there is no consensus on whether certain types of patients benefit more from a general, regional or mixture of the two types of anesthesia and anaesthesiologists have different priorities and preferences.[5] The onset of action of a peripheral nerve block is longer than a spinal (subarachnoid block), and the success rate of a satisfactory block is generally lower than for neuraxial blocks. However the cardiovascular stability and postoperative pain relief these regional blocks provide make them worthwhile techniques to perform especially in the critically ill patients.